F(x) = x² + x⁴
f(-x) = (-x)² + (-x)⁴ = x² + x⁴ = f(x) -- функція парна
f(x) = 1/x² + 2
f(-x) = 1/(-x)² + 2 = 1/x² + 2 = f(x) -- функція парна
f(x) = √(x² + 1)
f(-x) = √((-x)² + 1) = √(x² + 1) = f(x) -- функція парна
f(x) = |x³|
f(-x) = |(-x)³| = |-x³| = |x³| = f(x) -- функція парна
Одна коробка так как если в одну помещается 6 карандашей а всего их 5 то даже одна коробка заполнена не будет
..............................................................................
1)12/35
2)2целых 17/35
3)-3целых 5/24